Facial Lichen Planus Pigmentosus-Like Pigmentation Induced by Vicks VapoRub: A Case Report - Al-Husain KM; Alsebayel MM; Al-Breiki S; Almulhim N; Alsayyah A (Clinical, Cosmetic and Investigational Dermatology)
Khalid M Al-Husain,1 Musaed M Alsebayel,2 Sarah Al-Breiki,1 Nasser Almulhim,3 Ahmed Alsayyah4 1Department of Dermatology, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2Department of Dermatology, King Fahad University Hospital, Al-Khobar, Saudi Arabia; 3College of Medicine, King Faisal University, Al-Ahsa, Saudi Arabia; 4Department of Pathology, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Nasser Almulhim, King Faisal University, 36362, Al Mazrooa, Al-Ahsa, Eastern Province, Saudi Arabia, Tel +966536537773, Email almulhimnasser115@gmail.comAbstract: Lichen planus pigmentosus is a variant of lichen planus characterized by gray-brown hyperpigmented macules and patches occurring in sun exposed areas. Vicks VapoRub is an inhalant ointment frequently used to relieve symptoms of upper respiratory tract infections. We report a case of lichen planus pigmentosus induced by Vicks VapoRub and successfully treated with topical tacrolimus 0.1% cream.Keywords: lichen planus pigmentosus, Vicks VapoRub, tacrolimus, facial hyperpigmentation, lichen planus